SIMPLE METHOD TO CALCULATE FUTURE IPR IN GAS WELL - Mahda Eden Haq, Religious
The Future Inflow Performance Relationship (IPR) curve is a calculation that estimates the reservoir's ability to flow fluids in the future, taking into the decline in the reservoir's flow capacity over time. The construction of the IPR curve can be done using various methods, both through manual calculations and using software. Constructing the IPR curve requires data from the reservoir, which can be obtained from well testing. The ideal time for well testing is when the well is in a stable condition. This study discusses a new method proposed to construct the future Inflow Performance Relationship (IPR) curve for gas wells. The objectives of this research are to propose a calculation method for future IPR in dry gas reservoirs, compare the obtained future IPR results with existing methods, and validate the proposed method using available field data. The proposed method to predict future IPR in dry gas reservoirs is presented in an equation with a power regression approach. To compare the results, a comparison is made with the Golan & Whitson Method and the results of commercial software simulation. The comparison results show small differences between the future Absolute Open Flow (AOF) obtained using the proposed method compared to the Golan & Whitson Method and software simulation results. The proposed method shows a higher level of optimism compared to the Golan & Whitson Method and a lower level of pessimism compared to the software simulation results for future reservoir pressure conditions. Furthermore, validation is performed using field data, resulting in a comparison of future AOF between the proposed method and the Golan & Whitson Method. The comparison results show a small, more pessimistic from the Golan & Whitson Method for future reservoir pressure conditions.